2015
DOI: 10.1111/inm.12158
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity attitudes and preferences among inpatient adults with mental illness

Abstract: The life expectancy of adults with mental illness is worse than that of the general population and is largely due to poor physical health status. Physical activity has been consistently recommended for the prevention and management of many chronic physical health conditions and can also have benefits for mental health. This cross sectional study assessed the attitudes towards and preferences for physical activity among inpatient adults with mental illness, and differences by distress and gender. Self-report qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 34 publications
3
56
0
3
Order By: Relevance
“…The authors (Baker et al, 2014) found that self-report leisure screen time reduced after the intervention, and whilst encouraging the lack of a random sampling, absence of a control group and reliance upon self-report sedentary behavior are clear limitations. Recent research has established that walking is a preferred method of physical activity among people with psychosis (Fraser et al, 2015;. Thus, walking may be a strategy to not only increase physical activity but also to reduce prolonged sedentary behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The authors (Baker et al, 2014) found that self-report leisure screen time reduced after the intervention, and whilst encouraging the lack of a random sampling, absence of a control group and reliance upon self-report sedentary behavior are clear limitations. Recent research has established that walking is a preferred method of physical activity among people with psychosis (Fraser et al, 2015;. Thus, walking may be a strategy to not only increase physical activity but also to reduce prolonged sedentary behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that increasing daily steps might be an important strategy to mitigate metabolic risk in people with established psychosis. Moreover, walking is known to be a favored strategy for physical activity among people with schizophrenia and confers good health benefits [33,34]. Therefore, the combined message of 'sitting less and walking more' might offer health benefits for people with psychosis [35].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Barriers to physical activity were assessed using a 24-item questionnaire that assessed issues such as poor physical health, lack of skill, weight and lack of motivation. All three questionnaires have previously been used in research with adults with mental illness 189 . Participants indicated the extent to which they disagreed or agreed with each questionnaire item using a five point Likert scale (strongly disagree, disagree, unsure, agree and strongly agree).…”
Section: Physical Activity Attitudes and Barriersmentioning
confidence: 99%